Desempenho de coroas totais impressas em resinas composta obtidas por CAD/CAM: Estudo clínico, randomizado, controlado e triplo cego - Silva, Bianca Caroline (2024)
Objective: The aim of this triple-blind, randomized, prospective clinical trial was to evaluate the 6-month clinical performance of posterior full crowns made with CAD/CAM printing resins from two commercial brands: VarseoSmile Crown (Wilcos, Germany) and PriZma 3D Biocrown (Maquira, Brazil). Materials and Methods: Forty participants (10 men and 30 women) were rehabilitated with 64 CAD/CAM printed resin crowns. The material manufacturer was assigned randomly. After tooth preparation, a provisional acrylic resin crown was fabricated and maintained for an average of one week. For crown fabrication, an LCD W3D printer (Wilcos) was properly calibrated, and the parameters for VarseoSmile Crown and PriZma 3D Biocrown resins were set according to the manufacturer's recommendations. All crowns were cemented following preparation with alumina blasting (1.5 Bar; 50 microns), cleaning with 37% phosphoric acid (All Prime) for 45 seconds, application of a universal adhesive system (Ambar, FGM), and light curing for 20 seconds (Valo Cordless, Ultradent). The substrate underwent a dual resin cementation protocol (Allcem, FGM). After 6 months, color change (∆E00) and staining were evaluated in the printed crowns (primary outcome), as well as patient satisfaction with the definitive crown and its clinical performance based on the International Dental Federation (FDI) criteria regarding aesthetic, functional, and biological properties (secondary outcome). Results: There was no statistically significant difference between the groups in terms of color change. The clinical performance was equivalent between the resins, with patient satisfaction unaffected by the color changes. Conclusion: The evaluated resins demonstrated equivalent performance and were well accepted by patients, regardless of color changes. The results indicate that these resins could be promising alternatives for oral rehabilitation, offering benefits in terms of cost, time, and efficiency.